A Phenomenological Study on Indonesian Teachers’ Digital Competence in the Age of Education 4.0 - Jakaria; Elih; Iip; Asep; Faridah (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study examines teachers' digital competence in the technological era, its relevance to professional and educational contexts, and implications for educational development. Method: This research adopts a phenomenological approach to investigate and articulate the lived experiences of teachers regarding their digital competence in the era of technology. Result: The findings highlight four key dimensions of digital competence: (1) technological awareness, emphasizing the importance of technology in modern learning; (2) technical skills, encompassing mastery of digital tools and platforms; (3) digital collaboration, where informal learning enhances mutual support among teachers; and (4) adaptability, reflecting the ability to embrace new technologies. Novelty: A key novel finding is the critical role of informal learning in the workplace, which significantly contributes to enhancing teachers' digital competence. Effective strategies include continuous learning with mentorship, social support from colleagues and family, and leveraging digital media as a learning resource. Best practices such as workplace collaboration and family-supported learning foster holistic digital literacy development. Intrinsic motivation also drives successful technology adoption. This study recommends a holistic approach to developing teachers' digital competence through ongoing training, social support systems, and integrated technology use. Strengthening digital competencies promotes workforce readiness, enhances teaching quality, and improves student learning outcomes. In the context of Education 4.0, this development is pivotal for educational transformation and preparing the younger generation to thrive in the digital era.